Use of methylene blue for the detection of sentinel lymph node in breast cancer: a systematic review and meta-analysis - Parasuraman, Madhivadhanam; Giridharan, Bhanumati; Vijaylakshmi, . (International Surgery Journal, 2017)
Sentinel lymph node biopsy is the widely acceptable method for the examination of the breast cancer in the patients. This biopsy is considered as the best method for identifying the axillary involvement. Various dyes are used in this biopsy to find the sentinel lymph node. However, methylene blue dye (MBD) is considered to have a low risk of anaphylaxis, be cost effective and widely available. A systematic review and meta-analysis is performed on the utilisation of the methylene blue dye in the sentinel lymph node biopsy in the examination of breast cancer. Eight studies were appropriate for the inclusion criteria that were analysed systematically wherein meta- analysis is performed on studies which had ample data that comparatively analysed the efficiency of methylene blue. However, only two studies were selected for meta- analysis based on the availability of data. Systematic review reveals that methylene blue dye can be used as the best alternative when compared to other dyes in the detection of sentinel lymph node in the patients with breast cancer. However, the meta-analysis of two studies revealed no statistical significance defining the efficacy of methylene blue for sentinel lymph node detection.